Glutathione as a photo-stabilizer of avobenzone: an evaluation under glass-filtered sunlight using UV-spectroscopy. Issue 1 (13th November 2018) - Govindu, Panchada Ch V.; Hosamani, Basavaprabhu; Moi, Smriti; Venkatachalam, Dhananjeyan; Asha, Sabreddy; John, Varun N.; Sandeep, V.; Gowd, Konkallu Hanumae
Abstract : Glutathione significantly attenuates the photodegradation of avobenzone under glass-filtered sunlight. Abstract : Avobenzone is the most widely used UVA filter in sunscreen lotion and it is prone to degradation in the presence of sunlight/UV radiation. To overcome the photo-instability of avobenzone, various photostabilizers have been used as additives, including antioxidants such as vitamin C, vitamin E, and ubiquinone. In the present study, the well known antioxidant, glutathione, was evaluated for protecting avobenzone from photodegradation in the presence of glass-filtered sunlight. The features of glutathione as a skin whitener and a radical scavenger in cells have prompted the assessment of the photostabilzing activity of glutathione on avobenzone. Glutathione significantly attenuated the glass-filtered sunlight-induced degradation of avobenzone at equimolar or higher ratios of glutathione and avobenzone. Mutational studies have been undertaken to investigate the role of the thiol group and the isopeptide bond of glutathione on its photoprotection activity towards avobenzone. The thiol group of glutathione plays a vital role in exhibiting the photoprotection activity, which was further supported by the studies on photodegradation of avobonzone in the presence of β-mercaptoethanol. The dual role of glutathione as a skin whitening agent and a photostabilizer of avobenzone may be useful for the development of multipurpose cosmetic lotions.